Vice-Chancellor of UMP honors outstanding STPM students - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KUANTAN, 25 July 252023 - The Vice-Chancellor of Universiti Malaysia Pahang (UMP), Professor Dato' Ts. Dr. Yuserrie Zainuddin, had the opportunity to honour and share the joy with two outstanding Sijil Tinggi Persekolahan Malaysia (STPM) students at their respective residences.